PolyQ Database - A polyglutamine disease database - Estevam, Bernardo Alexandre Encarnação (2022)
Polyglutamine diseases are neurodegenerative disorders where the associated genes and translated protein products have an abnormal number of CAG triplets and glutamines, respectively. Mutated proteins with increased number of glutamines are usually correlated with neuronal dysfunction. Depending on the length of the pathogenic mutation, the effects on the normal cell mechanisms may be less or more severe, in other words, the severity of the disease is usually directly proportional with the number of glutamine repeats. There are 9 polyglutamine diseases: Huntington’s disease (HD), dentatorubral-pallidoluysian atrophy (DRPLA), spinal and bulbar muscular atrophy (SBMA) and the spinocerebellar ataxias (SCAs) 1, 2, 3, 6, 7 and 17. All these diseases are caused by the same mutation in their respective, and otherwise unrelated, genes – CAG triplet expansion. This abnormal triplet expansion is found in coding gene regions and later gives rise to the expanded glutamine sequence in the translated proteins. Mutated proteins with an increased number of glutamines often interfere with the normal cellular function by not performing their normal tasks and by compromising crucial cell mechanisms. PolyQ Database is a project that aims to be an online resource where everyone can learn about the most important features of every polyglutamine disease. Since information on each specific disease is usually scattered throughout various online sources, one of the main goals is to have all the most important information in one single online resource. The data available in PolyQ Database consists of simple and straightforward introductory information followed by more complex explanations about the genes and proteins affected in each disease, along with the pathophysiological mechanisms and cellular and biological deficits that may arise from these. This platform was done with hypertext markup language, cascading style sheets and JavaScript for the front-end (what the user interacts with). The back-end structure was entirely made with python Django framework. All the data stored for each disease was initially stored in an object oriented SQlite3 database created with Django but was later imported to a Microsoft SQL server. To obtain a scientific database structure with consistent and constant slices of information, the same data was presented for each polyglutamine disease. For each condition, the topics presented are: introduction, first description, epidemiology, causative gene, codified protein (structure, domains, functions and intracellular localization), pathophysiology and clinical manifestations (neuropathology, other signs and symptoms). The PolyQ Database can be found at https://polyq.pt/, where all the information gathered from various sources is presented, along with added supplementary pages, including a contact and authors pages, and a home page to search the diseases using either a search engine or disease tags.